2004
DOI: 10.2135/cropsci2004.1546
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pericarp Cell Wall Components in Maize Weevil Resistance

Abstract: The maize weevil (MW), Sitophilus zeamais (Motsch.), is a storage pest that causes serious losses in maize (Zea mays L.) in developing countries. This study was conducted to investigate the role of pericarp cell wall components as factors that contribute to MW resistance in nine genotypes of tropical maize. Six susceptibility parameters to MW were measured and related to cell wall components such as simple phenolic acids, diferulic acids (DiFAs), hydroxyproline‐rich glycoproteins (HRGPs), and nutritional and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
127
2
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(155 citation statements)
references
References 25 publications
(45 reference statements)
18
127
2
8
Order By: Relevance
“…Although genotypes were not statistically different for protein content (Table 1), a closer look at the best 5 and worst 5 genotypes revealed a tendency for genotypes with higher protein content to be resistant (based on the classification of the genotypes done at CIMMYT, Zimbabwe). This is consistent with what other investigators have found (Derera et al, 2001;Dhliwayo and Pixley, 2003;Garcia-Lara et al, 2004). The fact that protein content did not have a definite relationship with physical resistance parameters in this study may indicate that there are other resistance factors in maize studied.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although genotypes were not statistically different for protein content (Table 1), a closer look at the best 5 and worst 5 genotypes revealed a tendency for genotypes with higher protein content to be resistant (based on the classification of the genotypes done at CIMMYT, Zimbabwe). This is consistent with what other investigators have found (Derera et al, 2001;Dhliwayo and Pixley, 2003;Garcia-Lara et al, 2004). The fact that protein content did not have a definite relationship with physical resistance parameters in this study may indicate that there are other resistance factors in maize studied.…”
Section: Discussionsupporting
confidence: 92%
“…Progeny emergence tended to be higher in susceptible genotypes than in resistant ones (Garcia-Lara et al, 2004). In this study, the susceptible check had the highest number of the total F 1 emergence, numbering up to 87 weevils, against the experimental mean of 13 weevil emergencies.…”
Section: Discussionmentioning
confidence: 45%
“…Resistant maize genotypes are usually characterized with no/very low F 1 weevil progeny emergence after a long period of time (64 days) while susceptible maize varieties are characterized with greater numbers of F 1 WPE in a very short time period (32 days) under favorable humidity (70±5) and temperature (28±2) conditions (Dhliwayo and Pixley, 2004). Basing on the literature gathered from García-Lara et al (2004) it can be postured from this study that, hybrids (CZH131022, CZH131003 and CZH132064) that exhibited low F 1 weevil progeny emergence might contain phenolic compounds that might have discouraged faster rate of weevil oviposition and development. There is also a possibility that these hybrids are lacking nutrients that are required to support weevil oviposition and development.…”
Section: F1 Weevil Progeny Emergence (F 1 Wpe) Percentage Grain Weigmentioning
confidence: 88%
“…Mechanisms and level of Mandizvidza et al 4151 resistance to weevil damage varies among maize genotypes and this is determined by the composition of particular kernels of a maize variety. Some varieties (weevil resistant) contain different compounds that discourage their successful utilization as hosts by insect species while others (susceptible) contain compounds favorable for weevil oviposition (García-Lara et al, 2004). These compounds vary greatly among maize varieties and can be passed on from one generation to another.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, muchos de estos métodos demandan tiempo, costo y personal especializado. La implementación de nuevos métodos permitiría una evaluación más eficiente y efectiva de la resistencia de las variedades a las principales plagas de postcosecha (Bergvinson & García-Lara, 2004).…”
Section: Percentage Of Damaged Grainsunclassified